Chomsky and Lakoff: from cognition to language and politics, and back - Diodato, Filomena (Rivista Italiana di Filosofia del Linguaggio, 2023)
The paper aims to compare two distant yet close conceptions of politics and political communication, that of Noam Chomsky, which matured since the second half of the last century, and that of George Lakoff, which came into vogue between the 1990s and 2000s. Chomsky and Lakoff are the heroes of the Linguistics Wars which redefined the physiognomy of US linguistics and cognitive science and also personify, each in his way, the figure of a public intellectual. Nevertheless, dealing with politics and communication, both fail to untangle the link between cognition, language, and propaganda: Chomsky moves, albeit contradictory, from heaven to earth, i.e., from the scientific investigation of language and mind to the non-scientific realm of historical events, whose analysis is entrusted to the citizen endowed with a Cartesian common-sense; Lakoff takes, instead, the reverse path, outlining a political mind that embrains the ideologies and consequently proposing cognitive activism which aims at reframing people’s brain. Both approaches flow into an outdated, reductionist communication model, entailed in both first and second-generation cognitive science, which does not ponder the complexity of political and communicative practices enacted by semiotic-political animals.